Effects of increasing feeding level during late gestation on sow and litter performance - N W Shelton; C R Neill; Joel M DeRouchey; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2009)
A total of 108 gilts and sows (PIC 1050) and their litters were used over 2 gestation and lactation periods to determine the effect of increasing late gestation feeding level on sow and litter performance. Treatments were structured as a 2 × 2 factorial design with main effects of feeding level (0 or 2 lb of extra feed from d 90 to farrowing) and parity group (gilts or sows). The trial was conducted for 2 successive parities, with gilts and sows remaining on the same treatment for both parities. For the first gestation and lactation period, gilts had increased (P<0.001) backfat thickness on d 35, 90, and 112 of gestation and at farrowing compared with sows but had increased (P<0.001) lactation backfat loss. Increasing late gestation feed increased (P<0.001) weight gain from d 90 to 112 in both gilts and sows. There were late gestation feeding level × parity interactions observed (P<0.04) for ADFI and total feed intake for the overall lactation period. This was due to gilts having decreased lactation ADFI when fed extra feed in late gestation, but when sows were fed extra feed, lactation ADFI increased. Increasing feeding level in late gestation also increased (P<0.04) total feed cost. A feeding level × parity interaction was observed (P<0.04) for average weight of total born and live born pigs. Increasing feeding level in late gestation increased piglet birth weight in gilts but decreased piglet weight in sows. Gilts had increased (P<0.02) number and total weight of the total born, live born, and number after fostering compared with older parity sows. Gilts weaned larger (P<0.002) litters and had increased (P<0.03) total litter weaning weight compared with older parity sows. At weaning, sows had a decreased (P<0.002) weaning to breeding interval compared with gilts, and a late gestation feeding level × parity interaction was observed (P<0.03) for conception rate. Gilts that received increased late gestation feed had a greater conception rate than those maintained on the same level, whereas a decrease in conception rate was observed when sows received increased late gestation feed. During the subsequent lactation period, a feeding level × parity interaction was detected (P<0.005) for lactation backfat loss. This interaction was reflective of an increase in backfat loss in parity 2 sows as the late gestation feeding level was increased and a decrease in backfat loss in parity 3 and older sows with increasing late gestation feeding level. A feeding level × parity interaction was detected (P<0.02) for lactation weight loss; parity 2 sows lost a greater amount of weight when late gestation feeding level was increased, whereas similar weight losses were observed between treatments in parity 3 and older sows. Total born and live born numbers and total litter weight were greater (P<0.006) in parity 2 sows than in parity 3 and older sows. A late gestation feeding level × parity interaction was observed (P<0.01) for average weight of both total born and live born pigs because of an increase in piglet birth weight as parity 2 sows were supplemented with 2 lb of additional feed in late gestation with a slight numeric decrease in parity 3 and older sows. Additional feed in late gestation increased (P<0.02) average piglet weaning weight, with a large improvement observed in parity 2 sows. Total number weaned and total weight at weaning were increased (P<0.004) in parity 2 sows compared with parity 3 and older sows. This trial indicates that adding extra feed to late gestation diets increased feed cost with no benefit in sow performance. In gilts, conception rate and litter weaning weight were increased during the second parity, but no other benefits were found.; Swine Day, Manhattan, KS, November 19, 2009
Keywords: Swine day; 2009; Kansas Agricultural Experiment Station contribution; no. 10-014-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1020; Gestation feeding; Lactation; Sow; Swine